Critical amino acid residues regulating TRPA1 Zn2+ response: A comparative study across species - Matsubara, Masaki; Muraki, Yukiko; Suzuki, Hiroka; Hatano, Noriyuki; Muraki, Katsuhiko (The Journal of biological chemistry, 2024)
Cellular zinc ions (Zn2+) are crucial for signal transduction in various cell types. The transient receptor potential (TRP) ankyrin 1 (TRPA1) channel, known for its sensitivity to intracellular Zn2+ ([Zn2+]i), has been a subject of limited understanding regarding its molecular mechanism. Here, we used metal ion-affinity prediction, three-dimensional structural modeling, and mutagenesis, utilizing data from the Protein Data Bank and AlphaFold database, to elucidate the [Zn2+]i binding domain (IZD) structure composed by specific AAs residues in human (hTRPA1) and chicken TRPA1 (gTRPA1). External Zn2+ induced activation in hTRPA1, while not in gTRPA1. Moreover, external Zn2+ elevated [Zn2+]i specifically in hTRPA1. Notably, both hTRPA1 and gTRPA1 exhibited inherent sensitivity to [Zn2+]i, as evidenced by their activation upon internal Zn2+ application. The critical AAs within IZDs, specifically histidine at 983/984, lysine at 711/717, tyrosine at 714/720, and glutamate at 987/988 in IZD1, and H983/H984, tryptophan at 710/716, E854/E855, and glutamine at 979/980 in IZD2, were identified in hTRPA1/gTRPA1. Furthermore, mutations, such as the substitution of arginine at 919 (R919) to H919, abrogated the response to external Zn2+ in hTRPA1. Among single-nucleotide polymorphisms (SNPs) at Y714 and a triple SNP at R919 in hTRPA1, we revealed that the Zn2+ responses were attenuated in mutants carrying the Y714 and R919 substitution to asparagine and proline, respectively. Overall, this study unveils the intrinsic sensitivity of hTRPA1 and gTRPA1 to [Zn2+]i mediated through IZDs. Furthermore, our findings suggest that specific SNP mutations can alter the responsiveness of hTRPA1 to extracellular and intracellular Zn2+.